オーロラ リュウシ ノ カンソク - 松本, 治弥; マツモト, ハルヤ; MATSUMOTO, Haruya (国立極地研究所, 1975)
P(論文) An outline of the auroral particle detector which is planned to be flown in the Japanese Antarctic rocket experiments during IMS is presented. The detector uses a combination of curved plate electrostatic analysers and channel electron multipliers together with thin foils. It measures 0.1, 0.3, 0.5, 1, 3, 5keV electrons. The observable fluxes are 10^5-10^8/cm^2 s sr keV for all energies with the pitch angle resolution of 20°-30°. Measurements of proton flux are also under consideration. departmental bulletin paper